Make the World New : The Poetry of Lillian Allen - Allen, Lillian, 1951-; Allen, Lillian, 1951- (Laurier poetry series., 2021)
Lillian Allen is one of the leading creative Black feminist voices in Canada. Her work has been foundational to the dub poetry movement, which swept across the Black diaspora in the 1980s, taking roots/routes in Kingston, Toronto, and London and offering exciting sounds of protest and a careful, detailed documenting of everyday life as political praxis. Make the World New brings together some of the highlights of Lillian Allen's work in a single volume. It revisits her well-known verse from the celebrated collections Rhythm an' Hardtimes, Women Do This Everyday, and Psychic Unrest, while also assembling new and uncollected poems. Allen's poetry is incisive in its narration of Black life and its call to create new and different futures. Her work highlights the need for radical intersectional change as a process of social transformation. Allen's afterword, "Tuning the Heart with Poetry," includes the writer's reflections on her process and the social and cultural impact of the work. The introduction, by Ronald Cummings, engages with the duality of Lillian Allen's poetry in its written and spoken forms, and the give and take in committing poems to the page that "are not meant to lay still." He also reflects on the dynamism of Allen's dub poetry, where, for example, her portrayal of breaths and breathings take on new resonance in the era of Black Lives Matter and COVID-19.